Systematic Education Management And Conceptual Framework In Improving The Quality Of Education: Literature Review - Jemmy, Jemmy; Hendrilia, Yudi; Suharmono , Soni; Aji , Lexi Jalu; Oci , Markus; Ahyani , Edi (Universitas Pahlawan Tuanku Tambusai, 2023)
Education management is a good benchmark in the field of education, whether the quality of education really depends on management, many problems arise in the field of education because the goals and policies taken by education managers are inappropriate. To be able to solve these various problems, it is necessary to carry out research in this direction so that education is of good quality and has great meaning for the lives of Indonesian people. The purpose of writing this article is to find out the systematic education management and conceptual framework in improving the quality of education. This research is qualitative research in the nature of a library study which uses books, scientific articles and other literature as the main object. The result of this literature review is that quality management occurs because in a product, of course you want quality in the product so that customers are more attracted to buying it. In maintaining the quality of the product, of course there are steps to maintain the quality. This step or method is through management in the educational environment which is called quality management, because in quality management there is planning, supervision and orders to improve the quality. Based on this basis, to improve the quality of education it is necessary to have quality management in it